Komunikasi Dakwah Penyuluh Islam di Masyarakat Multikultural - Suhendri Suhendri (Al-Wa'iyah, 2025)
This study aims to analyze the communication strategies of Islamic preachers (penyuluh) in promoting social harmony within multicultural societies. In modern contexts, Islamic preaching functions not only as a means of religious transmission but also as a tool for strengthening social solidarity and cultural cohesion. This research employs a descriptive qualitative approach through library research, drawing on previous studies and communication sociology literature. The findings indicate that the effectiveness of Islamic preachers depends on their ability to apply adaptive, empathetic, and intercultural communication strategies. Moreover, the digital transformation requires preachers to act as multidimensional communicators capable of managing religious content in online spaces while maintaining the authenticity of Islamic messages. The social function of da’wah also contributes to character development, interreligious tolerance, and social integration. Therefore, Islamic preachers should enhance their digital literacy, cultural empathy, and ethical communication competencies so that da’wah remains spiritually relevant and socially impactful in building a harmonious, inclusive, and civilized society.